Heterocycles via Cross Dehydrogenative Coupling Synthesis and Functionalization - Srivastava, Ananya; Jana, Chandan K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the developments in the synthesis and functionalization of different heterocycles based on the formation of carbon-carbon (C-C) and carbon-heteroatom (C-X) bonds using cross-dehydrogenative coupling (CDC). Consisting of 13 chapters, the book systematically describes the advances in the synthesis and functionalization of nitrogen, oxygen, and sulfur-containing heterocycles. It also discusses the various mechanistic pathways to help readers gain an in-depth understanding of the CDC reactions of heterocycles. Lastly, in order to promote green chemistry, it addresses a range of metal-free CDC reactions of heterocycles - an area that has attracted significant attention in both academic and industrial research. .
Functionalization of aromatic N-heterocycles with C(sp3)-H sources via CDC reactions -- Functionalization of aromatic N-heterocycles via C(sp2)-H/C(sp2)-H CDC reactions -- The C-1 Functionalization of Tetrahydroisoquinolines via Cross-Dehydrogenative Coupling Reactions -- Cross-Dehydrogenative Coupling in the Synthesis and Functionalization of Fused Imidazoheterocycles -- Cross-Dehydrogenative Coupling of Carbonyls for Heterocycles Synthesis.
Keywords: Chemistry, Organic; Catalysis; Organic Chemistry; Catalysis